أثر أزمة منطقة اليورو على الإيرادات النفطية للجزائر للفترة 2005 - 2012 - عبد اللاوي, عقبة (جامعة الوادي - University of Eloued, 2015)
على غرار أغلب الدول النامية تتميز الصادرات الجزائرية بالأحادية كون الطبيعة هي التي منحتها ميزة نسبية في إنتاج المحروقات والتي تُشكل نسبة 98% من هيكل الصادرات. وفي ظل بقاء طبيعة الاقتصاد (الريعي) وهيكل الصادرات في المدى القصير والمتوسط على حاله، مع عدم وجود استراتيجيات واضحة من أجل العمل على تغير هذا الهيكل، يبقى الاقتصاد الجزائري ونموه، والسياسات الاقتصادية المنتهجة مرتبطة ارتباطا وثيقا بتقلبات أسعار البترول والطلب عليه عالميا. وهذه الدراسة تُسلط الضوء على فترات الأزمة باعتبارها وضع استثنائي يؤثر على مراكز نشوئها ماليا واقتصاديا، مُسببا حالات من الركود الاقتصادي الذي قد يرتقي ليبلغ سقف الكساد، مؤثرا على أغلب المتغيرات الاقتصادية الكلية الوطنية، ومنتقلا من صبغة محلية إلى نطاق إقليمي أو عالمي عبر قنوات عدوى اقتصادية، لعل من أهمها قناة الصفقات التجارية، والتي تعتبر الصادرات ضمنها من أهم مداخل التأثر والتأثير. وعليه فإننا سنتتبع في هذه الدراسة أثر أزمة منطقة اليورو على الإيرادات النفطية الجزائرية، وذلك من خلال النموذج القياسي الذي تمت صياغته. Like most developing underdeveloped countries Algerian exports is characterized by unilateralism that nature granted a comparative advantage in the production of hydrocarbons, that accounted for 98% of the export structure. In light of the survival nature of the rentier economy and structure of exports in the short and medium term as it is, with no clear strategies for action to change this structure, the Algerian economy and its growth, and economic policies made known remain closely linked to fluctuations in oil prices and global demand. This study highlights the periods of crisis as an exceptional situation affects tion centers financially and economically, causing cases of economic recession, which may live up to a ceiling of recession, affecting the most national macroeconomic variables, and moving from local dye to a regional and global scale through economic infection channels, perhaps the most important is the business deals channel, which considered exports including one of the most important vulnerability and impact entrances. Accordingly, we follow in this study the impact of The euro zone crisis on the Algerian oil revenues, and through the econometric model formulated.
مقال
Keywords: الأزمة المالية، الإيرادات النفطية، سعر الصرف، التضخم.; financial crisis, oil revenue, exchange rate, inflation.